NUMERICAL SIMULATION ANALYSIS OF NATURAL GAS AND HYDROGEN CO-FIRING AT PESANGGARAN DIESEL GAS POWER PLANT - Akif Miftahun Najakhi, Muhammad
In the energy sector in Indonesia, power plants contribute the most CO2 emissions. To achieve the target of zero carbon emissions by 2060, PT PLN made a policy of converting gas diesel power plants to non-carbon fuel-based plants. One of the efforts that can be taken in this transition period is to conduct co-firing. Hydrogen has the potential as an alternative non-carbon fuel in co-firing with carbon fuels because of its characteristics as a carrier of large amounts of energy. The focus of the co-firing study in this research is PLTDG Pesanggaran. Modeling and simulation of natural gas and hydrogen co-firing were done with Ansys Forte software. The hydrogen mole fraction in co-firing varies from 10% to 100% in 10% increments. The analysis showed that the average maximum cylinder pressure and temperature increased with the increase of hydrogen mole fraction. The duration of ignition delay continues to grow while the duration of combustion continues to decrease. Fluctuations occur in power per cylinder of the engine and thermal efficiency, but the specific fuel consumption (SFC) continues to fall. On the other hand, CO2 and CO emissions can be reduced as the hydrogen mole fraction increases, with the most significant reduction of 95% and almost 100% occurring at 100% hydrogen mole fraction, respectively. NOx emissions increased due to the average maximum cylinder temperature increase, exceeding the 350 mg/Nm3 threshold at 90% hydrogen mole fraction. Considering the engine's combustion characteristics, performance, and exhaust emissions, the maximum recommended hydrogen mole fraction in co-firing is 40%.